An Analysis of Setting Shift in Novel Megat by Rida K. Liamsi - Syafrial Syafrial; Hadi Rumadi; Oki Rasdana (Proceedings of AICS - Social Sciences, 2017)
The aim of this study is to describe whether there is a shift in function of setting in novel Megat by Rida K. Liamsi from the former story Megat Sri Rama. This study took novel Megat by Rida K. Liamsi as the sample of the research. The method of this research is descriptive method. The shift in function of setting that occurred from novel Megat Sri Rama into novel Megat by Rida K. Liamsi was described. This shift is related to the habit of function of setting in real life. If the shift of setting happen in these two stories, so the events in the story would be effected. The results of the analysis of novel Megat by Rida K. Liamsi were some functions of settings were shifted if they were related to the events that happen due to the author's view of the past setting. So, it can be concluded that the place and time setting become the virtue of the events of a story. In the field of language and literature learning, language has the power to describe events that occur supported by the context of the setting. Without setting, the readers will have difficulties to describe the theme, moral, character and mandate in the story. The cultivation of these values greatly contributes to the education of character and literacy today. Keywords: shift, setting, novel.